PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU - Aini, Ilmi; Hariri, Hasan; Rini, Riswanti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
The aim of this article is to examine the influence of the transformational leadership style of school principals and organizational culture on teacher performance in schools. The articles used in this literature review were obtained through Google Scholar by using keywords such as